Quality of Dental Education among Students after Graduation: A Perspective Study - Rabia Khan; Sana Khan (ziauddin University, 2024)
Background: Dental education is a demanding profession and limited resources and hinders the quality of education. Therefore, evaluation of perceptions of dental graduates in dental schools is significant to improve the dental education. The aim of this study gathers information regarding student's perception of dental education after their graduation, their level of satisfaction with quality of education received. Methods: This was a cross sectional descriptive study (n=110) conducted in Frontier Dental and Medical College and Islamic International Dental College. A self-administered questionnaire regarding the student's perception of educational curriculum and programme with their competence and satisfaction was assessed. Students and recent graduates participated in the study. The statistical analysis was achieved by using SPSS 20.0 (USA), and frequency distributions were implemented for each variable. Fisher's exact test was applied to compare the perception of final year students with house officers. The level of significance was set at p<0.05. Results: In the overall verdict judgment in both the colleges, only 25 (23%) of participants were generally satisfied with the quality of their dental education. Additionally, when asked regarding clinical training that if it prepared them to work independently as a dental practitioners, the participant's 27 (25%) of respondents has agreed with the statement and felt ready for working independently. Conclusion: This study on dental student's perceptions of the undergraduate curriculum lightens on the various aspects of the curriculum to make efforts in improving the undergraduate curriculum and to train the dentists and teaching staff more knowledge and skills. Keywords: Dental Education; Perception; Education; Dental School; Curriculum.